Автоматизація моніторингу виконання робіт будівельної компанії - Кієнко, Д. В. (ХНУРЕ, 2024)
This research focuses on integration of the modern information technologies in the construction industry, specifically in the context of monitoring the execution of construction works. The project utilizes the Python programming language for implementing the server-side data processing functionality. PostgreSQL is chosen for database management due to the numerous of advantages it provides compared to other SQL implementations, which align with the project's needs. The website's web interface is developed using the React framework due to its ability to create interactive single page applications, HTML 5 for structuring the content, and CSS 3 for styling.
Keywords: автоматизація моніторингу; будівництво